2022
DOI: 10.3390/su14094958
|View full text |Cite
|
Sign up to set email alerts
|

Back and Forth on Sustainable Development: A Focus on Healthcare Organisations

Abstract: The sustainability of healthcare systems represents a relevant target of the 2030 Sustainable Development Goals Agenda. Nevertheless, academic research has neglected to study healthcare systems when focusing on the transition toward sustainable healthcare. This study addresses this gap by investigating the implementation of the sustainable development (SD) principle in the Italian healthcare system, in light of international and national institutional discourses on SD. A questionnaire-based survey has been dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The research was conducted with the implementation of the systematic review methodology to achieve the aim of the paper [7], as the study is devoted to filling in the gap in the existing literature by determining, analyzing, and summarizing the previously obtained results regarding the efficient mechanisms of shifting towards a sustainable way of organizing and managing healthcare organizations' activities, which in turn leads to reaching the SDGs. Additionally, recent papers have suggested studying organizations' social, economic, and environmental practices that lead to an increase in the overall level of sustainability [8][9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research was conducted with the implementation of the systematic review methodology to achieve the aim of the paper [7], as the study is devoted to filling in the gap in the existing literature by determining, analyzing, and summarizing the previously obtained results regarding the efficient mechanisms of shifting towards a sustainable way of organizing and managing healthcare organizations' activities, which in turn leads to reaching the SDGs. Additionally, recent papers have suggested studying organizations' social, economic, and environmental practices that lead to an increase in the overall level of sustainability [8][9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it has been proven that management spending has a positive and direct relationship with the level of performance of medical organizations; more specifically, increased spending reduces the waiting time for patients. Moreover, studies have found evidence that medical performance also improves with an increase in management expenditures [8,[45][46][47]. Therefore, improvements in management practices are positively associated with the mortality level and overall financial performance, measured as income per bed.…”
Section: Improvements In Management Practicesmentioning
confidence: 99%
“…Most of the innovations focused on integrating such technologies in the process to achieve the ideal of sustainability. The institutionalization inside the structure of diverse systems implies the integration of diverse technologies in making decisions, protocols, and policies that ultimately modify health care quality, from the diagnosis to the organization of care [11][12][13].…”
Section: Integration Of Developments Sustainable Goals: Technology Ed...mentioning
confidence: 99%
“…Budgeting is an important part of managing money in public health. Giving money to different activities and programs based on their goals and desired results is part of this process [3]. Planning, analyzing, and setting priorities carefully is needed for budgets to work well so that resources are used wisely and people's wants are met.…”
Section: Introductionmentioning
confidence: 99%